GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 65 species occurrences available in GBIF matching the query: TaxonKey: Undaria pinnatifida (Harvey) Suringar Geometry: POLYGON((63.19 -5.01,63.19 54.42,173.41 54.42,173.41 -5.01,63.19 -5.01)) HasGeospatialIssue: false. The dataset includes 65 records from 11 constituent datasets: 1 records from Naturalis Biodiversity Center (NL) - Botany. 2 records from Australia's Virtual Herbarium. 1 records from NMNH occurrence DwC-A. 1 records from Natural History Museum (London) Collection Specimens. 45 records from Ibaraki Nature Museum, Algae collection. 2 records from NSW herbarium collection. 5 records from University of British Columbia Herbarium (UBC) - Algae Collection. 2 records from MGC Herbarium of University of Malaga (Spain): MGC-Algae dataset. 1 records from Lund Botanical Museum (LD). 3 records from Bernice P. Bishop Museum. 2 records from Cryptogamy collection (PC) of the Muséum national d'Histoire Naturelle (MNHN - Paris).
Keywords: GBIF; biodiversity; species occurrences